Hybrid quadratic DC-DC boost converter for fuel cell-powered electric vehicle with wide voltage gain and low voltage stress - Dinakaran, K. P.; Jebaselvi, G. D. Anbarasi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The need to cut carbon emissions and the worry about global warming will be two of the major issues of the twenty-first century. Globally, academics are researching renewable energy sources, with the majority of their efforts focused on the converter side, which is critical to contemporary society. For energy conversion, fuel cells provide an alternative to internal combustion engines. Despite the fact that typical DC-to-DC converters experience high stress and minimal voltage rise, the bulk of research focuses on voltage lift. Researchers from all around the globe use DC-DC converters to control the voltage of fuel cells. If the targets are fulfilled, more switches will be placed, resulting in higher losses. The boost-cuk converter in this research has a high voltage gain and low switching strain. Initially, this contributed to the development of self-control. Switching losses are reduced when just one switch is used. A DC-DC converter is employed in this research to transform the electricity provided by fuel cells. The alternating supply is then sent to the brushless direct current (BLDC) motor by the PWM inverter. The work starts by building MATLAB simulation blocks. Finally, Simulink is used to display the simulated output waveforms of the intended converter.